Tanggung Jawab Pemerintah Daerah Kota Ambon Dalam Penyediaan Tempat Pembuangan Sampah Berskala Reduce, Reuse Dan Recycle Di Kawasan Pemukiman - Leiwakabessy, Daniella Christy; Rugebregt, Revency Vania; Tita, Heillen Martha Yosephine (Faculty of Law, Universitas Pattimura, 2025)
Various activities in residential areas of Ambon City generate waste that requires serious and sustainable management. In this regard, the authority of the Ambon City Government to procure 3R-scale (Reduce, Reuse, Recycle) waste bins has not been implemented in accordance with the provisions of the prevailing laws and regulations, even though such procurement is an essential requirement in addressing waste management problems within settlements. Based on this, the legal issue raised in this study concerns the responsibility of the Ambon City Regional Government in providing 3R-scale waste disposal facilities in residential areas.The purpose of this study is to analyze and examine the legal responsibility of the Ambon City Regional Government in carrying out its authority related to the provision of 3R-scale waste management facilities in residential areas, as well as to identify strategic measures that can be implemented to achieve sustainable waste management in accordance with environmental protection principles.This study employs a normative juridical method, which emphasizes the study of legal norms, legal principles, and the provisions of applicable laws and regulations. The analysis is based on primary and secondary legal materials, using both a statutory approach and a conceptual approach. Data were collected through library research and analyzed qualitatively to answer the problem formulation systematically and argumentatively.The results of this study indicate that the Ambon City Regional Government has not yet implemented the regulations related to waste management in accordance with established procedures. Residential areas within the jurisdiction of Ambon City still lack environmentally friendly and well-distributed waste disposal facilities. Therefore, strengthening the capacity of local governments, formulating policies that involve community participation, and ensuring transparent supervision are strategic measures to guarantee the fulfillment of citizens’ rights to a clean and healthy environment.